Fostering digital dialogue: a case study of government social media initiatives in advocating social participation - Atalia Praratya; Vidi Sukmayadi; Dinda Nur Griya Kamil (Penerbit Universiti Kebangsaan Malaysia, 2024)
Engagement with the public and promoting social participation have emerged as essential aspects of democratic governance which have resulted in the focus towards social media by the Indonesian government. The role of social media has become increasingly vital for the Indonesian government and its governing agencies to reach and accommodate broad and diverse publics. Unfortunately, in developing nations, particularly Indonesia, using social media in government institutions to engage with the people and provide services is still deemed inconsistent and uneven. Hence, this case study explores an Indonesian provincial government's social media initiatives that have been nationally acknowledged as successful in strategies of fostering digital dialogue to facilitate social participation and could potentially become an exemplary implementation model for the country. The authors conducted a focus group discussion with public information and social media officials. Generally, the findings demonstrate how regional governments, with solid backing from the top leader and a well-designed strategic plan, could leverage social media platforms to meet public expectations while advancing democratic governance. Furthermore, the findings indicate that the social media initiatives undertaken by the provincial government have facilitated public participation, ensuring that citizens are heard and can actively participate in governmental decisions that impact their needs. This paper contributes to the existing literature on government public relations by highlighting the government's role in advocating democratic and participatory governance.